Implementation of Pivot Table Analysis to Identify Sales Trends in E-Commerce Business at SMK Al Amanah - Nirmala, Endar; Mulyati, Sri (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service activity was conducted at SMK Al Amanah as an effort to enhance participants’ abilities in processing and analyzing sales data in e-commerce businesses. The available sales data were generally used only as archives, thus providing limited valuable information for business strategy development. Therefore, this activity aimed to improve students’ understanding and skills in processing and analyzing e-commerce sales data through the application of Pivot Table analysis. The implementation method included a preparation stage, the delivery of materials on e-commerce concepts and data analysis, hands-on practice in creating and using Pivot Tables with spreadsheet applications, as well as mentoring and discussions. Sales datasets were used as practice materials to provide participants with real experience in grouping and summarizing data based on specific variables, such as time, products, and sales volume. The results showed that participants were able to independently create Pivot Tables, understand sales patterns and trends, and identify best-selling products and peak sales periods. In addition, the activity enhanced participants’ analytical thinking skills and data literacy in the context of digital business. Participants developed a stronger understanding of the importance of data analysis as a basis for decision-making in e-commerce businesses. In conclusion, the application of Pivot Table analysis in this Community Service activity was effective in improving the competencies of SMK Al Amanah students in data processing and e-commerce business, as well as in supporting data-driven learning.